(untitled) (Tribhuvan University Journal of Microbiology, 2018)
Objectives: In order to determine the prevalence of multi-drug resistance along with AmpC and metallo-β-lactamase producing P. aeruginosa, a six month cross-sectional study was carried out at Shahid Gangalal National Heart Center. Methods: A total of 756 clinical specimens were analyzed for bacteriological profile. The bacterial isolates were identified by cultural and biochemical techniques. Antibiotic susceptibility testing of the isolates was performed by Kirby-Bauer disc diffusion method. MDR isolates were screened and tested for MBL and AmpC production. Ceftazidime resistant isolates were tested for MBL and Cefoxitin resistant isolates for AmpC. Results: Among all the clinical samples analyzed, P. aeruginosa was detected in 75 samples (9.92%). Antibiotic susceptibility testing showed Imipenem as the most effective drug with susceptibility of 76% followed by Piperacillin-Tazobactam (74.7%) and Piperacillin (41.3%). Out of 75 P. aeruginosa isolates, 53 (70.6%) of them were found to be resistant to at least three out of four anti-pseudomonal agents, thus were considered as MDR. Out of 53 multi-drug resistant P. aeruginosa (MDRPA), all were resistant to ceftazidime whereas 85% (45/53) were resistant to cefoxitin. Out of 53 isolates, 11 (20.75%) showed positive result for MBL. Similarly, 7 out of 45 i.e. 13.2% were found to be AmpC producers. Conclusion: This study signified the high prevalence of MDRPA which is an alarming rate. Also multiple β-lactamase producing P. aeruginosa were detected which can further complicate the treatment options. Regular monitoring of antibiotic susceptibility and rational use of antibiotics would be helpful in eliminating the outbreaks of multiple β-lactamase producing MDRPA.